Droga Niemiec do paktu Ribbentrop-Mołotow i sprawy polskie (wydarzenia i interpretacje) - Kornat, Marek (Pamięć i Sprawiedliwość, 2008)
The article deals with the genesis of the co-operation of the Third Reich with the Soviet Union in 1939. This issue has been analyzed on numerous occasions by historians but it is still controversial and disputable. This is connected with several problems: 1. What were the short-term and long-term intentions of Adolf Hitler towards Poland in 1938–1939? 2. Who was the initiator of the pact: Hitler or Stalin personally, the German Auswärtiges Amt or the People’s Commissariatfor Internal Affairs of the USSR? 3. What were the aim and the function of the Molotov-Ribbentrop Pact in the political and war strategy of the Third Reich? What goals was the pact supposed to achieve as far as the political ideas of Hitler are concerned, and what was the real role of the pact in the reality of 1939?The close German-Soviet relations were the process of several stages. The first stage started with the Polish government rejecting the German demands and with the British guarantees issued for Poland in March 1939. The second stage lasted from May till July 1939, that is: simultaneous steps taken by the governments of western powers and Germany diplomacy to gain the support of the USSR. The third and fi nal stage is August 1939 when Adolf Hitler personally took over theinitiative which resulted in organizing decisive talks on strategic interests of the Third Reich and the USSR. Actually, Stalin was always ready to negotiate with Germans as he perceived Germany ‘one of the countries of bourgeoisie’ that is neither better nor worse than the western powers. Hitler made a fi nal decision to sign the agreement with the Soviet Russia not earlier than in June 1939. However, it is probable that he started considering such a step in the spring. In the German Ministry of Foreign Affairs people still followed the Bismarck way of thinking that is the desire to establish the German-Russian condominium over Central and Eastern Europe.The Polish issues played a fundamental role in the genesis of the German-Soviet relations. Hitler thought that the political normalization of relations with Poland in 1934 and diplomatic co-operation of Berlin and Warsaw on many issues in 1934–1938 seemed promising. That is why he thought that one day the future Poland would become the ally of the Great Germany in. That was probably the main condition imposed on Poland by Hitler. The demands concerning the return of the Free City of Danzig to Germany and exterritorial motorway via Polish Pomerania presented for the fi rst time in October 1938 by the German minister offoreign affairs were to lead to the formation of stronger bonds between Poland and Germany. Poland was to play a role of a vassal-type neighbour. Polish government rejected such a perspective. Hitler condemned that decision. He decided to reach a tactical agreement with the USSR, and the Molotov-Ribbentrop pact was to lead to a complete annihilation of Poland.